(untitled) (World Science, 2021)
In article the strict requirements imposed to products of light industry by the international EKO-TEX-100 standard are considered, characteristics of the properties of biological safety of clothes produced from textile materials and a knitted cloth are given, the question of existence of an electro statistical charge in products of light industry against increase oncological and nervous a disease and its influence on health of the person is discussed.